Senegal Groundnut Value Chain Competitiveness and Prospects for Development - World Bank (World Bank, Washington, DC, 2017)
The groundnut value chain is of major economic, social and political importance in Senegal. Most rural households grow the crop, and its transport, storage or processing is a key source of nonfarm employment in both formal and informal enterprises. Senegal’s groundnut sector was originally developed by colonial authorities, using a monopoly over exports to control the domestic market. For groundnuts in Senegal, the French-owned oil processor was nationalized to form SONACOS in 1975, which proved increasingly costly to operate and was eventually privatized in 2005 to form SUNEOR in 2007. That too has suffered increasing losses and in January 2010 the government finally ended the monopoly system, allowing farmers to sell to competing firms for either direct export or processing. Despite turmoil in the groundnut processing sector, groundnut production itself remains a mainstay of the rural economy. This report builds on a number of previous studies to inform ongoing changes in the sector. Most notably, we build on the diagnostic analysis of the groundnut value chain that was conducted in 2014 (World Bank 2015) and addressed a set of key reform proposals. The focus of this report is detailed in its Terms of Reference (Annex 4).